HEARTY Cast-Iron and Skillet COKING : 101 Easy-to-Make, Feel-Good Recipes - Schaeffer, Anne (Mount Joy, PA : Fox Chapel Publishing Company, Inc., 2023)
Hearty Cast-Iron and Skillet Cooking is filled with tasty and easy Dutch oven and skillet meals that will wow your friends and family. Perfect for bringing home cooking with you to a relaxing camping or cabin getaway, this cookbook presents more than 100 delicious cast-iron skillet recipes that are sure to please all appetites all day long. Ranging from cinnamon rolls with blueberries and creamy mac and cheese to eggplant parmesan, Italian beef stew, and so much more, you'll have plenty of wholesome cooking ideas for breakfast, starters, sides, lunches, dinners, and desserts to make. Make savory and cozy cuisine that will make your gathering one to remember!
Includes index
Keywords: Cast-iron cookware; Dutch oven cooking; Skillet cooking